Pemberian Remisi Bagi Koruptor di Indonesia Dalam Perspektif Hak Asasi Manusia - Rosalia, Rosalia; Wagiman, Wagiman (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
The right to obtain remission in Indonesia is contained in Law Number 22 of 2022 concerning Corrections. Regarding the right to remission is contained in Article 34A paragraph (1) letter a of Government Regulation Number 99 of 2012 concerning Conditions and Procedures for Implementing the Rights of Prisoners. The problem that occurs is whether corruptors who harm the state and Indonesian society deserve remission. The issue of Justice Collaborator is also interesting to discuss because it has many pros and cons. This research is a doctrinal research with a statutory and conceptual approach. Legal materials are obtained from legislation, to strengthen the analysis, this research also uses some empirical and normative research results. The analysis of data is carried out using the content analysis method which focuses on the study of laws and regulations regarding remission. This study argues that the elimination of the requirement to become a Justice Collabolator for perpetrators of corruption will eliminate human rights because the right to obtain remission is not given immediately but there must be mandatory conditions and procedures that must be met for perpetrators of corruption. based on Article 29 paragraph (2) and Article 28J paragraph (2) of the 1945 Constitution that restrictions on the fulfillment of human rights can only be carried out for reasons carried out under the law and stipulated by law. Meanwhile, the elimination of the requirement to become a Justice Collaborator